Anxiety Level of Patients Undergoing Oral Surgical Procedures - Acharya, Sudeep; Joshi, Sandhya; Pradhan, Amita (Journal of Nepal Health Research Council, 2018)
Background: Evidences on dental anxiety scale are essential in dental practice for better service delivery. The main objective of this study was to determine the anxiety level of patients undergoing oral surgical procedures and explore its associated factors. Methods: This was a cross sectional study enrolling 142 patients. Semi structured questionnaire based on Corah’s dental anxiety scale was prepared and administered to gather information. Descriptive statistics, chi- square test and independent t- test were used to analyze the data. Results: Sixty nine percent were feeling relaxed in waiting area. Nine patients (6.3%) were afraid of persons in white attire. About 17% reported that they were afraid of sound of dental apparatus. Many participant (81%) expected better outcomes of their dental procedures. When waiting for their procedure at the waiting area, about 50% stated to sense restlessness. Nearly 56% felt unease while waiting at dental chair. Nearly 70 % of cases had less than 7 dental anxiety scale score indicating low anxiety to dental procedures, 23.2% showed moderate anxiety with score of 7 to 9 and 7% showed high anxiety by scoring 10 or more out of score of 15.Average dental anxiety scale scores did not vary as per age differences. The anxiety scores for both sexes were alike. Conclusions: Even though anxiety level was low among the cases undergoing oral surgical procedure, being in waiting area and dental chair raises their apprehension.